DUALISME SUDUT PANDANG REVITALISASI KEPATIHAN (STUDI KASUS: JALAN SURYATMAJAN - IRFAN ADI SUKMAWAN; Purwoko .; Achmad Taufiq (Journal of Politic and Government Studies, 2015)
AbstractRevitalization is one way to maintain the old buildings that still maintained its authencitiy. Therevitalization must have positive and negative impacts. Positive impact of revitalization,among others caring for the building in oder look more beutiful, and negative impactscompromising the surrounding community. In the revitalization of the harness there must beconflict steakholder.This research, Dualism view point kepatihan revilization (Ssuryatmajan road corridor) aimsto determine the causes of differences between civil society and kepatihan office. In addition,it is also explain what efforts were made Kepatihan to handle the conflict. This research usesqualitative research methods with techniques of data collection through in-depth interviews(depth interviews) and analysis of documentation.The results showed that the social conflict in Revitalization Kepatihan Office forest happenedsince colonial times untill this time is caused by some factors. Social conflict is caused by fourfactors: differences in perception, differences in interests (economic), changes in values andrecognition of land ownership. Kepatihan has done a variety of ways to resolve and reduce theconflict, such as socialization of Revitalization, education Sultan Ground, providing supportand so on. Based on the result, this research recommends some alternatives for conflictresolution, through a collaborative approach with open communication with the public space,management of forest resources are more participatory, improving the quality of humanresources, and strengthening the management of organization.Keywords: different view, different interest, conflict resolution.